Paciente femenino con 73 años de edad con ulcera por decúbito grado 3 y desnutrición moderada. - Romero Anchundia, Tamara Jaerly (2021)
Through this case study, it can be verified about the solution that was proposed to a 73-year-old patient where he presents in his history problems of cerebrovascular accident for which he was discharged 2 years ago, currently the patient shows presence of edema, pressure ulcers in their upper and lower limbs, physical decompensation and leukocytosis involvement are observed. Patient arrives at the care unit through the emergency area, unconscious, for which medical personnel assist so that the patient reacts and remains awake, to perform a corresponding physical evaluation where a normal cephalic head was shown, symmetric chest, conserved expandability, no It uses accessory muscles, the right subclavian venous route is present in its neck, its abdomen is soft depressible, not painful on palpation, air-fluid noises (RHA) are heard, in the sacral region it presents third-degree ulcers, it has the presence of edema in the upper and lower extremities, shows ulcer lesions in both ankles, the doctor in charge sends him to do some complementary tests to arrive at an analysis and determine an appropriate treatment for the patient. Patient goes to a control with a nutrition professional for presenting an inadequate nutritional status, therefore, intercedes with nutritional treatment and recommendations on the corresponding diet for the patient, is given a hyperprotein diet in order to recover his physical condition and biology. A nutritional monitoring and control are implemented where the evolution of the patient is recorded, with a gain of 11 kilograms in 6 months of nutritional consultation and a favorable record for complementary examinations.